Understanding the catalysts and obstacles: the path to performance budgeting in Iraq's higher education sector - Mat Daud, Zaidi; Khudhair, Ali Hussein; Mustafa @ Abdul Razak, Hasri; Jasin, Ali Naeem (Scientifia Canada, 2024)
Amid growing pressures for efficient governance, performance budgeting (PB) emerges as a crucial reform in developing regions, particularly Iraq, where traditional models have faltered. This study in- vestigates the adoption of PB within Iraq's higher education sector, using a quantitative approach. Data from 401 respondents were analyzed through Partial Least Squares Structural Equation Modeling (PLS- SEM) to explore the influence of internal and external pressures and identify adoption barriers. Results revealed that internal pressures significantly promote PB adoption, while external pressures underscore the global trend towards accountable budgeting. However, persistent barriers, such as institutional re- sistance and resource scarcity, impede effective adoption. These findings underline the necessity for tailored approaches to PB in contexts like Iraq, offering insights for policymakers on overcoming these challenges.